1998
DOI: 10.1017/s002531540004474x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Macroalgal Carbohydrates By The Marine Amoeba Trichosphaerium Sieboldi

Abstract: ^University Marine Biological Station Millport, Isle of Cumbrae, Scotland, KA28 OEG Trichosphaerium sieboldi is a marine amoeba with a cosmopolitan distribution. The ability of three strains, from different geographical regions, to digest a range of macroalgae was investigated. Prior to these experiments, methods were developed for the axenic cultivation of T. sieboldi. Algae included Fucus vesiculosus, F. spiralis, Laminaria digitata, L. saccharina, Mastocarpus stellatus, Palmaria palmata, Porhyra sp., and Ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In so doing, they are exploiting a unique niche. Moreover, at least one marine amoeba has been shown to be capable of directly digesting particulate carbon (Rogerson et al 1998). The large numbers of surface‐associated naked amoebae in mangroves, the wealth of new species, and the importance of mangroves in the cycling of coastal carbon and nutrients, all indicate that the ecological role of mangrove protozoa, and amoebae in particular, deserves further consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In so doing, they are exploiting a unique niche. Moreover, at least one marine amoeba has been shown to be capable of directly digesting particulate carbon (Rogerson et al 1998). The large numbers of surface‐associated naked amoebae in mangroves, the wealth of new species, and the importance of mangroves in the cycling of coastal carbon and nutrients, all indicate that the ecological role of mangrove protozoa, and amoebae in particular, deserves further consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Out of all the heterotrophic protists, amoebae are unique in that they are intimately associated with surfaces and may graze niches spatially unavailable to other microconsumers. Moreover, there is some evidence that amoebae have unusual enzymes that enable them to digest a wide range of microbial prey and even macroalgal carbon (Rogerson et al 1998). The ecological implications of these grazing protozoans are yet to be appreciated but their seemingly ubiquitous distribution indicates that they are a largely overlooked group of protozoa deserving of further attention.…”
mentioning
confidence: 99%
“…For example, Sherr (1988) demonstrated that some estuarine flagellates can use high molecular weight polysaccharides found in surface waters, and one amoeba, Tnchosphaerium sieboldi, has been shown to be capable of digesting intact seaweeds (Polne-Fuller et al 1990, Rogerson et al 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Its members are primarily described from marine environments. They are among algae eating protists playing an important ecological role in the marine environment [ 15 , 16 ]. The taxonomy of Trichosphaerium is poorly understood mainly due to the dramatic morphological transformations it undergoes during its life cycle.…”
Section: Introductionmentioning
confidence: 99%